Adipocyte Hypertrophy in Stromelysin-3 Deficient Mice with Nutritionally Induced Obesity - Lijnen, H. R.; Van Hoef, B.; Frederix, L.; Rio, M.-C.; Collen, D. (Thrombosis and Haemostasis, 2002)
Several matrix metalloproteinases (MMPs), including the stromelysins MMP-3 and MMP-11, are expressed in adipose tissue. To investigate a potential role of MMP-11 (stromelysin-3) in adipose tissue development, five-week-old male wild-type mice (MMP-11+/+) or mice with deficiency of MMP-11 (MMP-11−/−) were fed a high fat diet (HFD, 42% fat) for 15 weeks. Haematologic parameters, including white and red blood cells, platelets, haemoglobin and haematocrit, and metabolic parameters including glucose, triglycerides and total cholesterol were not different for both genotypes. At the time of sacrifice, the body weight of the MMP-11-/mice was higher than that of the MMP-11+/+ mice (36 ± 1.4 g versus 29 ± 0.9 g, p = 0.0002). The weight of the isolated subcutaneous (SC) and gonadal (GON) fat deposits was also higher in MMP-11−/−mice (620 ± 150 mg versus 280 ± 28 mg for SC fat, and 970 ± 180 mg versus 430 ± 62 mg, p < 0.05, for GON fat). Adipocytes in MMP-11−/−adipose tissue were hypertrophic as compared to MMP-11+/+ adipocytes (volume of 57 ± 12 × 103µm3 versus 31 ± 2.4 × 103µm3 for SC fat, and 100 ± 18 × 103µm3 versus 57 ± 7.6 × 103µm3 for GON fat; both p < 0.06). In nutritionally induced obesity models in mice a potential role of the fibrinolytic system was suggested in adipocyte hypertrophy. The hypertrophy observed in this model is, however, not related to changes in fibrinolytic parameters, as suggested by our finding that levels of t-PA, u-PA and PAI-1 antigen as well as t-PA and u-PA activity were not different in SC or GON adipose tissue extracts of both genotypes. As the main biological function of MMP-11 remains unknown, it is not clear whether the adipocyte hypertrophy in MMP-11−/−adipose tissue is directly related to the deficiency or to other pathways affected by MMP-11.
Keywords: Obesity; stromelysin; adipocyte